The Role Of Parents In Developing Emotional Intelligence In Early Children - Rahmadani, Chyndy Vatika (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2024)
Education involves various aspects for continuity, defense, and enhancement of life. The role of parents in early childhood education is crucial as a child's development today affects their future. Knowledge about child development helps parents and teachers in planning optimal developmental efforts. This study uses a qualitative method to explore how parents focus on emotional intelligence, with data collection conducted through literature review. Preschool education is a valuable investment for preparing a healthy and intelligent future generation, including cognitive and emotional intelligence. Emotional intelligence involves recognizing, understanding, and managing emotions, which is essential for solving future problems. However, not all parents are aware of the importance of emotional development in early childhood. The research findings highlight the roles of parents as educators, caregivers, facilitators, and role models in the emotional intelligence development of children in Krobokan Village, Semarang Barat